Evaluation of fungal degradation of wheat straw cell wall using different analytical methods from ruminant nutrition perspective. (13th March 2019) - Nayan, Nazri; van Erven, Gijs; Kabel, Mirjam A; Sonnenberg, Anton SM; Hendriks, Wouter H; Cone, John W
Abstract: BACKGROUND: White rot fungi have been used to improve the nutritive value of lignocellulose for ruminants. In feed analysis, the Van Soest method is widely used to determine the cell wall contents. To assess the reliability of this method (Method A) for determination of cell wall contents in fungal‐treated wheat straw, we compared a combined monosaccharide analysis and pyrolysis coupled to gas chromatography with mass spectrometry (Py‐GC/MS) (Method B). Ruminal digestibility, measured as in vitro gas production (IVGP), was subsequently used to examine which method explains best the effect of fungal pretreatment on the digestibility of wheat straw. RESULTS: Both methods differed considerably in the mass recoveries of the individual cell wall components, which changed on how we assess their degradation characteristics. For example, Method B gave a higher degradation of lignin (61.9%), as compared to Method A (33.2%). Method A, however, showed a better correlation of IVGP with the ratio of lignin to total structural carbohydrates, as compared to Method B (Pearson's r of −0.84 versus −0.69). Nevertheless, Method B provides a more accurate quantification of lignin, reflecting its actual modification and degradation. With the information on the lignin structural features, Method B presents a substantial advantage in understanding the underlying mechanisms of lignin breakdown. Both methods, however, could not accurately quantify the cellulose contents – among others, due to interference of fungal biomass. CONCLUSION: Method A only accounts for the recalcitrant residue and therefore is more suitable for evaluating ruminal digestibility. Method B allows a more accurate quantification of cell wall, required to understand and better explains the actual modification of the cell wall. The suitability of both methods, therefore, depends on their intended purposes. © 2019 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.